2014
DOI: 10.2174/1871530313666131122151325
|View full text |Cite
|
Sign up to set email alerts
|

Specific Nutritional Supplement (Supportan<sup>&#174;</sup>) in the Supportive Care of the Radio-Chemotherapy Treatment of Head and Neck Cancers: Biochemical Parameters. Preliminary Study

Abstract: In this preliminary study of few patients, we have observed a potential usefulness of Supportan(®) in the compliance of concurrent RT-CHT in patients with H&N cancers; moreover, its administration was useful to maintain the initial biochemical nutritional profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Fifty articles examining various nutritional compounds were identified, 49 from PubMed and 1 from Embase. 12 Reports included 1 study on activated charcoal, 13 1 study on β-glucan, 14 2 studies on multinutrient formulations, 15 , 16 2 studies on an amino acid–rich oral formulation, 17 , 18 1 study with folic acid with B 12 , 19 5 studies on vitamin E, 12 , 20 - 23 17 intervention studies containing minerals, 24 - 40 and 21 studies with glutamine ( Table 2 ). 41 - 61 Moreover, 25 clinical trials were identified examining honey alone or in combination as a prophylaxis/intervention for oral mucositis ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty articles examining various nutritional compounds were identified, 49 from PubMed and 1 from Embase. 12 Reports included 1 study on activated charcoal, 13 1 study on β-glucan, 14 2 studies on multinutrient formulations, 15 , 16 2 studies on an amino acid–rich oral formulation, 17 , 18 1 study with folic acid with B 12 , 19 5 studies on vitamin E, 12 , 20 - 23 17 intervention studies containing minerals, 24 - 40 and 21 studies with glutamine ( Table 2 ). 41 - 61 Moreover, 25 clinical trials were identified examining honey alone or in combination as a prophylaxis/intervention for oral mucositis ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a small, open-label study, it was reported that oral or parenteral administration of a multinutrient formulation was well tolerated in patients with head and neck cancers treated with chemoradiotherapy without developing severe mucositis. 15 In another, multinutrient formulation composed of amino acids, omega-3 fatty acids, ribonucleic acids, vitamins, and antioxidants was shown to be associated with less severe mucositis in patients with head and neck cancers treated with chemoradiotherapy. 16 In 2 other studies that examined the same amino acid–rich oral formulation, the first study found that the formulation was associated with reduced severity of mucositis in squamous cell carcinoma treated with radiotherapy with or without chemotherapy when compared with no formulation administration.…”
Section: Resultsmentioning
confidence: 99%